Blockers of Hyperpolarization-activated Cyclic Nucleotide-gated channels exhibit antimuscarinic properties in human atrial cardiomyocytes. (10th June 2022) - Gencarelli, M; Laurino, A; Balducci, V; Spinelli, V; Cameli, M; Pecori, R; Vistoli, G; Matucci, R; Cerbai, E; Sartiani, L
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): M.I.U.R. PRIN 2017 to E.C and ECRF to L.S. Introduction: Ivabradine (Iva), Zatebradine (Zat) and ZD7288 (ZD) are blockers of Hyperpolarization-activated Cyclic Nucleotide-gated (HCN) channels, which play definite electrophysiological functions in cardiac pacemakers, working cardiomyocytes, peripheral and central neurons [1]. Among them, Iva is in clinical use as bradycardic agent for uncontrolled angina and heart failure with reduced ejection fraction. Accumulating evidence suggests Iva may have a more complex pharmacological profile, including targets different from HCN channels [2, 3]. Reports on experimental atrial fibrillation, detrusor contraction and bladder overactivity [4] led us to hypothesize that muscarinic receptors (mAChRs) may represent still unexplored targets of Iva and analogues. Present study was designed to identify the effect of Iva on acetylcholine-gated inward-rectifier K+-current (IKACh), the main effector of atrial mAChRs, and to assess whether Iva and analogues interact directly with human atrial and recombinant mAChRs. Methods: Patch-clamp recordings were performed on human atrial myocytes (hAMs) isolated from atrial appendages of patients in sinus rhythm. Competition and kinetic radioligand binding assays were performed on hAM preparations and on mAChR(1, 2, 3) expressed in heterologous systems. Results: Patch-clamp recordings on hAMs demonstrated Iva is able to suppress IKAch similarly to atropine, thus suggesting a functional antagonism of Iva on atrial mAChRs.  Competition binding assays on hAM membranes revealed Iva, Zat and ZD bind to mAChRs with affinity values close to those of muscarinic ligands carbachol (Cch) and gallamine (Gal). Competition binding assays on recombinant mAChR(1, 2, 3), which are functionally relevant in hAMs, showed all blockers are ligands for each single mAChR type with affinity values close to those of CCh and Gal. Finally, using dissociation binding assays on mAChR(2) lacking the allosteric binding site, we showed Iva and Zat behave as allosteric ligands with affinity values similar to Gal. Doking studies confirmed Iva and Zat, but not ZD, have the structural requirements necessary to interact with the allosteric and the orthosteric site of mAChR(2). Conclusions: This study demonstrates Iva directly interacts with mAChR expressed in hAMs, showing antimuscarinic activity on IKAch. This property is likely dependent on a double interaction of Iva with the orthosteric and the allosteric site of mAChR(2). Zat, but not ZD, shows similar binding properties compared to Iva. Our results identify a novel pharmacological target for Iva and analogues in human atria, which may have important consequences for the function of the healthy and diseased atrium.